Multitarget Therapeutic Potential of Mimosa pudica (Linn.) in Luminal-Type Breast Cancer: A Bibliometric, Network Pharmacology, and Molecular Docking Analysis - Anwar Rovik; Laelatul Afifah; Vania Uly Andyra (Universitas Tidar, 2026)
The growing burden of breast cancer and the limitations of current treatment strategies underscore theneed to identify alternative therapeutic approaches. This study investigated the multitarget therapeuticpotential of Mimosa pudica (Linn.) against luminal-type breast cancer using an integrated computationalframework that combined bibliometric analysis, drug-likeness and ADMET screening, networkpharmacology, gene expression analysis, and molecular docking. Bioactive compounds reported from M.pudica were evaluated in silico to assess physicochemical characteristics, pharmacokinetic properties, andpotential molecular targets. Predicted protein targets were further analyzed using protein–proteininteraction network analysis and visualized in Cytoscape to identify key pathways associated with breastcancer progression. The analysis identified multiple candidate compounds with favorable pharmacologicalprofiles and predicted interactions with proteins involved in critical biological processes, including cellcycle regulation, DNA metabolism, growth factor signaling, angiogenesis, migration, and invasion. Networkanalysis highlighted several hub proteins associated with luminal-type breast cancer, among which AURKAand CDK1 were prioritized for molecular docking based on network topology, pathway enrichment,biological relevance, and structural suitability. Molecular docking demonstrated favorable predictedinteractions between selected flavonoids—apigenin, galangin, kaempferol, diosmetin, and chrysin—andboth target proteins, with binding energies ranging from −7.6 to −8.9 kcal/mol. These ????indings providemechanistic insight into the potential molecular actions of M. pudica-derived compounds and support theirprioritization as candidate therapeutic molecules for further experimental investigation in luminal-typebreast cancer. Keywords: bibliometrics; luminal-type breast cancer; Mimosa pudica; molecular docking; multitargettherapy; network pharmacology